New key management scheme of wireless sensor networks based on key relation table - HUANG Hai-ping1; WANG Ru-chuan1; SUN Li-juan1; CHEN Zhi1 (Tongxin xuebao)
Aimed at some security properties on key management for multicast such as forward confidentiality,backward confidentiality,resisting conspiracy-analysis,expansibility and robustness,and furthermore the obvious character of en-ergy-constraint,a new key management scheme based on threshold mechanism ＆ key relation table was proposed,which mapped keys’ value onto the three-dimensional curves and surfaces.Although computing complexity increases within a little scale,the performance optimization of memory complexity as well as communication complexity were proposed.